World religions: Eastern traditions - Amore, Roy C.; Hussain, Amir; Oxtoby, Willard Gurdon (Oxford University Press, 2019)
"World Religions: Eastern Traditions provides students with an authoritative examination of religions of the Eastern world. In this contributed text, experts on Hinduism, Sikhism, Jainism, Buddhism, and Chinese, Korean, and Japanese religions employ extensive knowledge and rigorous research to thoroughly investigate each tradition. "Traditions at a Glance" boxes open each chapter to present key facts and figures in a manageable way for students. Maps, photographs, key dates timelines, boxes highlighting key concepts, sites, and textual excerpts as well as further reading lists help bring each tradition to life for students. Accessible and engaging, the text explores the origins, central teachings, divisions and branches, rituals and practices, influences on culture, and responses to modern challenges for each tradition"--